Explaining provincial government health expenditures in China: Evidence from panel data 2007-2013 - Xiao Tan (China Finance and Economic Review, 2017)
Background: Since the mid-2000s, the Chinese government has increased government health expenditures (GHE) significantly to address widespread complaints about health delivery. This study examines the real per capita provincial GHE over the period 2007-2013 to identify the determinants of provincial GHE during the most recent round of health reforms. Methods: A range of theoretically grounded socioeconomic indicators were collected from the China Statistical Yearbooks and then factored to reduce the number of highly correlated indicators. Maps were drawn to visualise the spatial patterns of key variables and fixed-effects regressions were run to test relationships between the real per capita provincial GHE and various variables. GMM estimators were used to address endogeneity problems. Results: Key determinants of provincial GHE in China include the real per capita budgetary deficits, economy, and industrial structure (two factors composed from an exploratory factor analysis). Increasing 1000 yuan real per capita budgetary deficits was expected to increase the real per capita GHE by 34 yuan. A one-unit increase in the economy was associated with a 249 yuan higher real per capita GHE, while a one-unit increase in the industrial structure was expected to decrease the real per capita GHE by 33 yuan. Conclusions: The findings of this study reveal a worrisome picture: potential inefficiencies of the central government's funding efforts and the overwhelming importance of economic development for GHE.
Keywords: 330; Government health expenditures; Panel data analysis; China